2017
DOI: 10.1080/0972060x.2017.1294999
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oil from Leaves ofSchinus molleL. Growing in Taif, KSA

Abstract: Ao Senhor meu Deus, que me permitiu chegar até aqui, me dando forças e saúde para superar as dificuldades, me protegeu e me mostrou o seu amor incondicional a cada dia. Eu não seria nada sem o seu amor e misericórdia.Ao meu orientador, Prof. Dr. Douglas Siqueira Chaves, o qual eu tenho orgulho de dizer que trabalhamos juntos desde 2013, e que toda minha experiência profissional em pesquisa eu devo a ele. Obrigada professor, pelos incentivos, apoio e dedicação na elaboração deste e de outros trabalhos. Obrigada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…and 2.56% in essential oil) were the major identified sesquiterpenes. Some previous studies reported that S. molle aerial parts and fruits essential oils were riches with monoterpenes (Abdel-Sattar et al, 2010;Gomes et al, 2013;Hayouni et al, 2008;Machado et al, 2019;Martins et al, 2014), while some other studies reported that sesquiterpenes were represented as the main constituents (Abdel-Hameed and Bazaid, 2017;Cavalcanti et al, 2015;Garzoli et al, 2019;Simionatto et al, 2011). Thus, the variations in the chemical compositions percentiles of S. molle fruits essential oil and n-hexane ext.…”
Section: Gc-ms Investigation Of S Molle Fruits N-hexane Extract and The Essential Oilmentioning
confidence: 96%
See 1 more Smart Citation
“…and 2.56% in essential oil) were the major identified sesquiterpenes. Some previous studies reported that S. molle aerial parts and fruits essential oils were riches with monoterpenes (Abdel-Sattar et al, 2010;Gomes et al, 2013;Hayouni et al, 2008;Machado et al, 2019;Martins et al, 2014), while some other studies reported that sesquiterpenes were represented as the main constituents (Abdel-Hameed and Bazaid, 2017;Cavalcanti et al, 2015;Garzoli et al, 2019;Simionatto et al, 2011). Thus, the variations in the chemical compositions percentiles of S. molle fruits essential oil and n-hexane ext.…”
Section: Gc-ms Investigation Of S Molle Fruits N-hexane Extract and The Essential Oilmentioning
confidence: 96%
“…In folklore medicine, the extracts of S. molle were documented as antitumor, astringent, antiviral, antioxidant, antimicrobial, antiinflammatory, digestive stimulant, diuretic, and wound healer activities (Gomes et al, 2013;Hosni et al, 2011;López et al, 2014;Malca-García et al, 2017;Martins et al, 2014). The previously chemical investigation studies of S. molle have been reported; it contains various chemical ingredients, including monoterpenoid, sesquiterpenoid, triterpenoids, tannins, and flavonoids (Abdel-Hameed and Bazaid, 2017;Ono et al, 2008). To the best of our knowledge, there were no reports on the chemical investigation of S. molle fruits growing in Taif City, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the phytochemical importance and the superior health benefits associated with essential oils, it has been recognized for many years as a great source of pharmaceutical agents, aromatherapy, massage oils, personal care products, beverages, and food additives . Using essential oils in many fields encouraged scientists to study the plants bearing essential oils from the chemical and pharmacological investigations to the therapeutic aspects . Essential oils of aromatic plants are obtained from different plant parts such as flower, buds, seed, leaves, and fruits through mainly distillation extraction processes by water or steam and sometimes together.…”
Section: Introductionmentioning
confidence: 99%